2000
DOI: 10.1095/biolreprod63.1.335
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Versus Metabolic Signals as Determinants of Seasonal Anestrus in the Mare1

Abstract: The objectives of this study were to compare the timing and mechanisms controlling the onset of anestrus in young and mature mares treated either continuously with melatonin and in those that remained untreated. Changes in body weight, subcutaneous body fat measured to provide an estimate of total body fat, and circulating concentrations of leptin were compared throughout the 1-yr experimental period. The results demonstrate that in young mares the timing of anestrus occurs significantly earlier in the year th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 13 publications
8
84
2
Order By: Relevance
“…This is the first demonstration in the bat that shows reduced leptin levels associated with the decline in reproductive activity during winter. The present study is in line with the reports from other seasonal animals, such as mares and siberian hamsters (Drazen et al 2000, Fitzgerald andMcManus 2000). The decreased leptin level during winter dormancy may reflect changes in energy availability and depletion of stored fat that may result in a loss of permissive signals to the hypothalamus, which, in turn, retards gonadal activity.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first demonstration in the bat that shows reduced leptin levels associated with the decline in reproductive activity during winter. The present study is in line with the reports from other seasonal animals, such as mares and siberian hamsters (Drazen et al 2000, Fitzgerald andMcManus 2000). The decreased leptin level during winter dormancy may reflect changes in energy availability and depletion of stored fat that may result in a loss of permissive signals to the hypothalamus, which, in turn, retards gonadal activity.…”
Section: Discussionsupporting
confidence: 92%
“…From this figure we recommend a synchronisation of the first mating period in March. Good nutrition and a winter lighting treatment could help to obtain a result, for maiden and barren mares, [50][51][52][53]. Indeed, the length of night induces the production of a proportional quantity of the melatonin hormone signalling the beginning of winter ovarian inactivity.…”
Section: B Langlois C Blouinmentioning
confidence: 99%
“…Moreover, melatonin levels of both mares were similar to that observed in the other mares that were noncyclic. The studies have shown that treatment of mares with melatonin does not advance the onset of seasonal anestrus in mature mares (14,18). This suggests that other factors exist to maintain estrus cycle in nonbreeding season in mares apart from melatonin even if a correlation exists between melatonin and progesterone levels during non-breeding season in this study.…”
Section: Discussionmentioning
confidence: 50%
“…The short day length characteristic of fall and winter causes an increase in the daily duration of melatonin secretion, and this result in decreased secretion of gonadotropic hormones and the cessation of ovulatory activity (14). During the non-breeding season, most of the mares maintain progesterone (P4) concentrations below 1 ng/ml which do not show estrus signs and have ovaries that are small and smooth (29).…”
Section: Introductionmentioning
confidence: 99%